Evaluating poro-elastic production drive mechanisms: Quantifying the potential contribution to well-rates and risk of core handling damage inflating pore-volume compressibility measurements - Ruud Weijermars (Energy Geoscience, 2025)
By analyzing core data from an offshore Gulf of Mexico reservoir and developing analytical solutions, it can be demonstrated that laboratory measurements on pore-volume compressibility include artifacts, leading to a misinterpretation of porosity and permeability trends. A systematic evaluation of poro-elastic changes in pore volumes (and quantifying any consequent fluid expulsion during reservoir compaction) suggests that poro-elastic relaxation may enhance fluid production rates from deep reservoirs by up to 25 %. This value may be inadvertently inflated if the core samples used for pore-volume compressibility measurements suffered from handling damage. Nonetheless, poro-elastic fluid expulsion from the pores in producing reservoirs can provide additional lift and thus may enhance the recovery factor. Therefore, the possible contribution to well performance from poro-elastic production drive mechanisms ought to be carefully evaluated in reserves estimation. Reversely, injection wells may encounter poro-elastic suppression of injectivity due to elastic resistance, which would adversely affect the storage coefficient. By integrating geomechanical reservoir response with traditional fluid production models, reservoir model predictions of production under pressure depletion and injection conditions will be more accurate. The new insights reported here are essential for optimizing well performance, improving reservoir management, and extending the economic life of geological reservoirs. However, caution is warranted regarding pore-volume compressibility measurements. To what degree laboratory measurements of pore-volume compressibility measure true values or mainly record handling damage could not be conclusively settled in the present study.